A Comparative Environmental Assessment of Direct, Indirect, and Mixed-mode Solar Dryers - Juma, Abraham Kiprop; Kurják, Zoltán; Beke, János (Journal of Central European Green Innovation, 2025)
The present study offers a comparative environmental assessment of direct, indirect, and mixed-mode solar dryers to identify the most sustainable drying technology. Solar dryers are promising alternatives to open sun drying and fossil-fuel-powered dryers. They are also well-suited for rural areas in developing countries due to the widespread availability of solar energy. This analysis focuses on material sustainability, carbon footprint, and drying and energy efficiency. Direct solar dryers (DSDs) are simple to construct and can be made using locally available materials. However, they suffer from poor temperature control and low efficiency, which can negatively affect the quality of food products. Indirect solar dryers (ISDs) offer better performance than DSDs but involve additional components, making them more expensive to construct. Mixed-mode solar dryers (MMSDs) have the shortest drying time and the highest drying efficiency. However, they also have the greatest environmental impact due to their complex structure and high material requirements. There is a need to balance affordability, environmental impact, and performance in solar dryer designs to serve rural farmers in developing countries effectively. Future studies should focus on integrating localized and eco-friendly materials into solar dryer construction.